HIRANYAGARBHA SEBAGAI ARKETIPE PENCIPTAAN: KAJIAN HERMENEUTIK KOSMOLOGI MĀNAVA DHARMAŚĀSTRA DALAM PERSPEKTIF G. PUDJA DAN TJOKORDA RAI SUDHARTA - Adnyana, Ida Bagus Putu; Redi, I Wayan (Sphatika: Jurnal Teologi, 2025)
Cosmology is not only a part of scientific knowledge, but can also be affiliated with religious knowledge, such as the Hindu religion, for example. In the Hindu view, cosmology not only discusses the universe in a material sense (sekala), but also all forms, both material and non-material (niskala). Hinduism affirms that there is a real, formless existence called Brahman, which is a metaphysical monistic reality yet rich in personification. In other words, cosmologically, this universe is one of His various forms, or in the dimension of the Mānava Dharmaśāstra teachings, it is called Hiranyagarbha. Therefore, this study aims to analyze the role and meaning of Hiranyagarbha as a universal archetype of creation in Hindu cosmology, with a focus on the narrative found in Chapter 1 of the Mānava Dharmaśāstra. This research explores how this concept is formulated and interpreted, especially in the context of Hindu theology in Indonesia through a hermeneutic lens. Using a qualitative approach and a philosophical-hermeneutic analysis method, this study examines primary and secondary texts to interpret the meaning contained behind the creation verses. The main finding shows that Hiranyagarbha is not merely a mythological entity, but an archetype, a universal fundamental pattern from which reality manifests. The interpretations carried out by translators and academics in Indonesia, such as G. Pudja and Tjokorda Rai Sudharta, become an important bridge that connects classic cosmological narratives with modern monotheistic theology, by explicitly equating Hiranyagarbha with the concept of Brahman or Hyang Widhi Wasa. This study concludes that this hermeneutic act not only translates the text, but also contextualizes and provides strong theological relevance for contemporary Hindus.